Implications of health conditions on rural soybean workers' quality of life - Jeane Cristina Anschau Xavier de Oliveira; Áurea Christina de Paula Corrêa; Roseanne Montargil Rocha; Ediálida Costa Santos; Renata Cristina Teixeira Beltrame; Angélica Pereira Borges (Associação Brasileira de Enfermagem, 2022)
ABSTRACT Objective: to analyze the implications of health conditions on rural workers' quality of life in the context of soybean production. Method: a cross-sectional study, with an intentional sample of 299 male rural workers. Data collection took place between October and December 2019. The following instruments were used: World Health Organization Quality Life-bref; Rural Workers' Living & Health Conditions questionnaire; International Physical Activity Questionnaire; Cut down, Annoyed, Guilty, and Eye-opener. They were analyzed via descriptive and inferential statistics, using bivariate (Mann-Whitney; Kruskal-Wallis) and multivariate tests (generalized additive models for location, scale and shape). Results: the presence of a diagnosis of morbidity, alcohol dependence, occupational accidents and absenteeism implied a decrease in workers' quality of life scores. Conclusion: the existence of unfavorable health conditions has a negative impact on rural soybean workers' quality of life.